Limitation Of Judicial Review Authority by Constitutional Court of the Republic of Indonesia Regarding Criminal Provisions in Laws - Amriyanto, Amriyanto; Nur, Rafika (Khairun Law Journal, 2018)
Decision of the Constitutional Court of the Republic of Indonesia Number 46/PUU-XIV/2016 which rejects the extension of meaning and scope of adultery, rape and fornication in Indonesian criminal law becomes polemic in society. This is because the acts are very contrary to the moral and religious values, and Pancasila as the ideology of the Indonesian nation. The limitation of judicial review authority by Constitutional Court of the Republic of Indonesia related to criminal provisions is the reason for not willing to take the exclusive authority of the legislator in the formulation of criminal provisions. On the other hand, the Constitutional Court itself often extends the meaning and scope of norms in laws unrelated to criminal provisions.